Calidad del ambiente en archivos y biodeterioro de soportes documentales - Guiamet, Patricia (2012)
This work presents the results obtained from the analysis of air quality and environmental parameters in two archives of La Plata: Archivo Histórico del Museo de La Plata (AHMLP) and Archivo del Departamento de Investigación Histórica y Cartográfica de la Dirección de Geodesia (ADIHC). Biodeterioration studies were performed to evaluate possible damage to documents stored. This research was corroborated by laboratory tests using a bacterial strain (Bacillus sp.) and two fungal strains (Scopulariopsis sp. and Fusarium sp.) commonly isolated from these archives, in order to assess the damage on the paper. The samples to analyze the microbial quality of air were taken using the technique of sedimentation in agar. In the laboratory, isolated strains were inoculated in mineral medium with filter paper aged (72 h at 105 º C, equivalents to 25 years of age) as a only carbon source. Development of biofilm on documents and paper samples from laboratory assays were observed at the scanning electron microscope. The results of hygrothermal measurements showed that AHMLP remains 94% of the records obtained in the measurements within the tolerance range of temperature and RH for the conservation of paper, while the ADIHC this value decreases to 86%. Microbial counts were higher in the air of ADIHC, which would be related to peaks of RH recorded. Laboratory tests showed damage to cellulose fibers and pigments excretion by fungal activity.